Surface characterisation and wetting properties of single basalt fibres. (15th January 2017) - Pucci, Monica Francesca; Seghini, Maria Carolina; Liotier, Pierre-Jacques; Sarasini, Fabrizio; Tirilló, Jacopo; Drapier, Sylvain
Abstract: Basalt fibres are claimed to show better high temperature resistance compared to glass fibres, suggesting better prospects to survive an end-of-life composite thermal recycling process while preserving an adequate reinforcing efficiency. It is well known that sizing agents affect impregnation of fibre reinforcements during composite manufacturing, which influences the overall mechanical behaviour of the resulting composites. However, with the exception of some studies about coupling agent effects on the adhesion between basalt fibres and matrix, no information are present in literature on the wetting characteristics of basalt fibres. The main contribution of this study is the analysis of the surface properties and wetting behaviour of basalt fibres with sizing optimised for both thermoset and thermoplastic matrices. Measurements of static contact angles were performed with a tensiometric procedure designed for singles fibres, in order to determine their surface energy and its components. Modifications of surface properties due to chemical treatments and high temperature exposure were also investigated and discussed.